2001
DOI: 10.1161/01.cir.103.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Infection in Circulating Human Monocytes Is Refractory to Antibiotic Treatment

Abstract: Background-Recovery of the intracellular bacterium Chlamydia pneumoniae from atherosclerotic plaques has initiated large studies on antimicrobial therapy in coronary artery disease. The basic concept that antibiotic therapy may eliminate and prevent vascular infection was evaluated in vitro and in vivo by examining the antibiotic susceptibility of C pneumoniae in circulating human monocytes, which are thought to transport chlamydiae from the respiratory tract to the vascular wall. Methods and Results-Blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(173 citation statements)
references
References 35 publications
5
165
0
3
Order By: Relevance
“…33 The absence of an effect of antibiotic treatment on vascular events may be due to ineffective treatment strategies not affecting Cp in circulating monocytes. 34 Also, it can still be argued that viral infections, not affected by macrolide treatment, are involved in atherogenesis, arterial thrombosis and plaque rupture. 35,36 Recently, Ad infections were considered to play a role in the development of obesity and are associated with plasma lipid abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…33 The absence of an effect of antibiotic treatment on vascular events may be due to ineffective treatment strategies not affecting Cp in circulating monocytes. 34 Also, it can still be argued that viral infections, not affected by macrolide treatment, are involved in atherogenesis, arterial thrombosis and plaque rupture. 35,36 Recently, Ad infections were considered to play a role in the development of obesity and are associated with plasma lipid abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…PBMC from the 610 study patients were separated in a Ficoll-Histopaque density gradient (Sigma, St Louis, MO, USA). 2 For C. pneumoniae detection, purified DNA was resuspended in 100 ml water and subjected to PCR using the HL-1/HR-1 primers that amplify a genomic 438-bp C. pneumoniae target sequence. For enhanced specificity, a nested PCR protocol was used with the nested oligonucleotide primer pair In-1 (5 0 -AGT TGA GCA TAT TCG TGA GG-3 0 ) and In-2 (5 0 -TTT ATT TCC GTG TCG TCC AG-3 0 ), which yield a 128-bp product.…”
Section: Study Populationmentioning
confidence: 99%
“…For confirmation, nonradioactive DNA hybridization was performed using oligonucleotide HM-1 3 0 -tailed with digoxigenin-11-dUTP/dATP (Roche Diagnostics) as the probe. 2 Sera were tested for C. pneumoniae-specific antibodies with a microimmunofluorescence (MIF) assay (IgG, IgA, IgM; Labsystems, Helsinki/Finland). MIF-anti-C. pneumoniae IgG titer X1 : 16 indicated previous C. pneumoniae infection.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It has been suggested that C. pneumoniae infection of macrophages is often in a persistent form, which explains the observed refractory behavior of C. pneumoniae infection to antibiotic treatment in cells of monocyte-macrophage line. 11,12 Thus, new treatments are needed to fight the chlamydial infections and avoid the treatment failures.…”
Section: Introductionmentioning
confidence: 99%